Karakteristik Fisik dan Organoleptik Sempol Ayam dengan Tepung Ganyong (Canna edulis) sebagai Pengganti Tepung Terigu - Ahmad Sofwatullah; Aaf Falahudin; Rachmat Somanjaya (Study Program of Animal Husbandry, Faculty of Agricultural, Universitas Majalengka, 2026)
This study aimed to analyze the effect of using ganyong flour (Canna edulis) as a substitute for wheat flour on the physical and organoleptic characteristics of chicken sempol, as well as to determine the optimal substitution level for producing the best product quality. The substitution was carried out at five levels: 0%, 25%, 50%, 75%, and 100% ganyong flour, using a Completely Randomized Design (CRD) with four replications. The observed variables included water holding capacity (WHC), tenderness, and organoleptic attributes such as color, taste, texture, aroma, juiciness, and panelist acceptability. Data were analyzed using analysis of variance (ANOVA), followed by Duncan’s Multiple Range Test (DMRT) for parametric data, and hedonic tests for organoleptic parameters.The results showed that before frying, ganyong flour substitution significantly improved color and maintained the taste and aroma without decreasing the texture quality. After frying, the substitution did not have a significant effect on any organoleptic attributes (P>0.05), but still produced the best physical outcomes. Treatment P4 (100% ganyong flour) yielded the highest WHC and tenderness values (P<0.05), and was still well accepted by the panelists. These findings indicate that ganyong flour has great potential as a substitute for wheat flour due to its ability to enhance the physical quality of chicken sempol, while also offering a healthier product and supporting local food diversification.